HUBUNGAN PANJANG TUBUH DAN RASIO PAPILLA DENGAN JENIS KELAMIN PADA IKAN GOBI (Sicyopterus macrostetholepis Blkr.) - Sari, Rona Taula (Universitas Tanjungpura, 2016)
Research about relationship of body length and ratio papilla with sex in goby fish (S. macrostetholepis Blkr.) has been done at Animal Structure and Developmental Laboratory, Biology Department, Faculty of Matematics and Natural Sciences, Andalas University, Padang, which purposed to analyse the relationship of body length and ratio papilla with sex of goby fish (S. macrostetholepis Blkr.). The samples were taken at wild stream area at Batang Kuranji river, Padang City. This reseach used descriptive method and data were analized by qualitatively and quantitatively. The results of investigation showed that in several goby fish (S. macrostetholepis Blkr.) with different sexÂ had the same ofÂ body length and the same of ratio papilla. So, there was not relationship between of body length and ratio papilla with sex. Keyword: Papilla, S. macrostetholepis Blkr.